Tutorial Action for the Development of Social Skills in University Students - Javier Napa, Anthony Johnson (2019)
This research was carried out to design tutorials on the care of undeveloped social skills of university students, through which they express their needs, feelings, preferences, opinions and rights, respecting others and as a consequence self-reinforcement is observed and the probability of obtaining external reinforcement is maximized. The study was approached from the interpretive paradigm, qualitative approach, the projective-holistic method as a systematic process. Diagnostic information was collected from students and tutors, through interviews and focus groups, focused on behavioral, personal and situational skills. From all of this, categories and subcategories were identified that allowed choosing strategies to meet the needs. As a result, it was demonstrated that social skills, an important aspect for insertion and work performance, have not been developed despite the existence of the accompaniment of tutors. Also, the strategies used in the tutorial actions are not adequate; therefore, they must be modified. Also, it was concluded that university institutions must carry out planning processes for tutorials after diagnosis.